Quinoxaline: A comprehension of current pharmacological advancement in medicinal chemistry - Suresh Kumar Suthar; Narendra Singh Chundawat; Girdhar Pal Singh; José M. Padrón; Yuvraj Kunwar Jhala (Elsevier, 2022)
Quinoxaline is a fused heterocycle ring template present in diverse pharmacophore and widely used in medicinal chemistry. Owing to its vast pharmaceutical profile, several quinoxalines analogous displayed their distinct pharmacological activities. In the last couple of years, researchers have established several quinoxalines analogous via green protocol, multi-component cascades, one-pot synthesis, and combinatorial pin-point approach using effective catalysts and reagents. It is being further researched to develop novel entities for the advantage of humankind. This insight focuses on the latest synthesis, advances of quinoxaline analogous, developed during the last decennial period (2010-2020). Herein, we review the synthesis of quinoxaline motifs, debating various facets of structure-activity relationship and their bioavailability.